Protocol for development and use of spike-in control for chromatin immunoprecipitation of chromatin-binding proteins in Schizosaccharomyces pombe - Jasbeer S. Khanduja; Mo Motamedi (STAR Protocols)
Summary: Chromatin immunoprecipitation (ChIP) assays provide quantitative information about the genomic localization of chromatin-binding proteins; however, their sensitivity is limited by several technical variables. Here, we present a protocol for developing and using Saccharomyces cerevisiae chromatin as an exogenous spike-in control for ChIP of chromatin-binding proteins in Schizosaccharomyces pombe. We describe steps for preparing and validating the spike-in control. We then detail the procedure for adding spike-in control to S. pombe chromatin in ChIP assay and its use in data normalization.For complete details on the use and execution of this protocol, please refer to Khanduja et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.